Are Non-Euro Area EU Countries Importing Low Inflation from the Euro Area? - Iossifov, Plamen (IMF Working Papers; Working Paper, 2014)
The synchronized disinflation across Europe since end-2011 raises the question of whether non-euro area EU countries are affected by the undershooting of the euro area inflation target. To shed light on this issue, we estimate an open-economy, New Keynsian Phillips curve, in which we control for imported inflation. Regression results suggest that falling food and energy prices have been the main disinflationary driver. But low core inflation in the euro area has also had a clear and significant impact. Countries with more rigid exchange-rate regimes and higher share of foreign value added in domestic demand have been more affected. The scope for monetary response to low inflation in non-euro area EU countries depends on concerns about financial stability and unanchoring of inflationary expectations, as well as on exchange rate regime and capital flows dynamics.